Non-dimensional correlations for design of eccentrically obliquely loaded footings on cohesionless soils. Issue 4 (1st October 2013) - Viladkar, M N; Zedan, Adnan Jayed; Saran, Swami
<x xml:space="preserve">Abstract</x> In this paper, a comprehensive parametric study has been carried out to evaluate the behavior of footings on cohesionless soils and subjected to eccentric-inclined loads considering the non-linear elastic soil behavior and the soil-footing interface characteristics. The methodology for ultimate load criterion reported by De Beer (1970) was chosen to calculate the ultimate bearing capacity of sand having a relative density of 84% and depth to width ratios of 0·0 and 0·5. The values of ultimate bearing capacity agree very well with those of Meyerhof (1956). A detail parametric study was undertaken for different widths of footings and for different values of depth to width ratio, eccentricity to width ratio, load inclination, factor of safety, and relative density of sand. Based on the data obtained from this parametric study, non-dimensional correlations have been developed for predicting the values of settlement, horizontal displacement, and tilt of eccentrically obliquely loaded footings. These correlations have been found to be independent of the size of footing, factor of safety, and depth to width ratio and are dependent on the eccentricity to width ratio of the footing and the inclination of the applied load. To use these correlations, the settlement of the footing subjected to central load is required which can be obtained using the conventional methods.